Ethnomedicinal plants potentially used in treatment of skin diseases in Bhandara district (MS), India - Humane, Pitambar (Ethnobotany Research and Applications, 2025)
Background: The Bhandara district in eastern Vidarbha, Maharashtra, India, remains underexplored in terms of its ethnobotanical heritage, despite being rich in floristic diversity. This represents the first systematic documentation of ethnomedicinal plants used in the treatment of skin diseases in the region. The study aims to preserve traditional knowledge that is rapidly declining among the older generation of healers. Methods: Ethnomedicinal data were collected from 24 informants (19 males and 5 females; aged 51-80 years) using structured questionnaires and semi-structured interviews. Information recorded included vernacular names, plant parts used, preparation methods, dosages, and associated precautions. Quantitative ethnobotanical indices, including Use Value (UV), Relative Frequency of Citation (RFC), Informant Consensus Factor (ICF), and Fidelity Level (FL), were calculated to assess the relative importance of species and agreement among informants. Results: A total of 261 angiosperm species, representing 218 genera and 85 families, were documented for use against 24 categories of dermatological or skin ailments. Fabaceae (34 spp.), Malvaceae (15 spp.), Apocynaceae (14 spp.), Asteraceae (12 spp.), and Euphorbiaceae (10 spp.) were the most represented families. The highest UV and RFC values were recorded for Azadirachta indica (UV 2.04, RFC 1.00), Curcuma longa (UV 2.0, RFC 1.00) and Butea monosperma (UV 1.92, RFC 1.00). Leprosy, wounds, and boils were the categories with the highest informant consensus (ICF=0.94-0.98). Of the 261 species recorded, 12 exhibited ICF values greater than 0.9, indicating strong agreement among informants on their dermatological efficacy. Leaves were the most frequently used plant part (132 citations), typically prepared as paste or decoctions for topical application. Conclusions: Indigenous healers in Bhandara district maintain extensive knowledge of plant-based skin remedies, but this knowledge is at risk of being lost as intergenerational transmission declines. The plant species with high UV and FL should be prioritized for phytochemical and pharmacological validation. The findings contribute significantly to the regional ethnomedicinal record and highlight the importance of scientific validation before these remedies are incorporated into evidence-based healthcare systems. Keywords: Ethnobotany, Traditional medicine, Skin diseases, Quantitative indices, Bhandara district, Maharashtra.